Healing at a Distance: A Cross-Sectional Study on the Impact of Telewoundcare in Burn Recovery - Juris Jansons; Ilze Berzina; Piotr Nowak (Journal of Wound Research and Technology, 2025)
Background: Burn injuries, especially first-degree burns, remain a significant global health issue. Comorbidities such as diabetes require careful attention to wounds for successful recovery. Telewoundcare, a novel remote wound care system, has been proposed as a potential improvement in wound care outcomes. However, its use on burn wounds, especially in patients with chronic conditions, has not been sufficiently studied. Purpose: This study sought to assess the outcome of using Telewoundcare on first-degree burns at Liepaja Regional Hospital, Latvia, and compare it to the outcomes of traditional care. The study also aimed to assess the impact of smoking, diabetes, hypertension, and nutritional status as comorbidities on the healing of burn wounds. Methods: The study used a sample of 70 burning adult patients with first-degree burns. The patients were separated into two groups, one utilizing Telewoundcare and the other using traditional care. Patient data regarding smoking, comorbid conditions, and nutrition were recorded. The primary outcome measured was burn wound healing 1, 2, and 3 months post-treatment, through assessment of wounds visually and measuring the healing time. Results: The results revealed that smoking wishing caused substantial delays in wound healing, mostly in the Telewoundcare subgroup (OR=1.85, p=0.03). Conversely, no significant differences were detected in healing outcomes across stratified treatment groups for factors such as age, nutritional level, or accompanying illness (p>0.05). Although Telewoundcare was suitable for the management of first-degree burns, it was not more effective than conventional care in this study. Conclusions: While Telewoundcare demonstrated an ability to expand access to burn care, it did not surpass conventional care in healing outcomes. The most significant determinant of wound healing was the patient's smoking status. More research is needed with larger populations and longer durations to adequately evaluate the sustained impact of Telewoundcare on burn wound treatment over time